Wh quantifier float in German. (16th August 2022) - Doliana, Aaron
Abstract: This article investigates the syntactic distribution of the German quantificational particle known as "invariant alles " ('all'). The generalization that emerges is that, given a derivation, alles occurs in any position occupied by an Ā chain link of the "associate" of alles, that is, the phrase that alles "modifies." The article concludes that alles forms a deep constituent with its associate and that therefore instances of nonadjacent alles are derived transformationally, specifically by some stranding procedure. Floating analyses and adverbial analyses of quantifier float are argued to be insufficient to explain the generalization. Three types of argument are presented in support: (a) the distribution of alles is a subset of its associate's; (b) alles blocks derivations when it occurs in a position in which its associate would also block the derivation; (c) alles is sensitive to the kind of movement that its associate undergoes, in that it can occur in tails of Ā movement but not in tails of A movement. Further implications are that wh  movement proceeds successive‐cyclically through (presumably) vP in German, that tails of A and Ā movement can be distinguished by alles, and that object scrambling is necessarily A movement in German.